Incidence of Arterial Hypertension in People With Periodontitis and Characterization of the Oral and Subgingival Microbiome: A Study Protocol - Martínez-García, Mireya; Castrejón-Pérez, Roberto Carlos; Rodríguez-Hernández, Adriana Patricia; Sandoval-Motta, Santiago; Vallejo, Maite; Borges-Yáñez, Socorro Aída; Hernández-Lemus, Enrique (Frontiers in Cardiovascular Medicine, 2022)
Cardiovascular diseases are the leading cause of morbidity and mortality worldwide. High blood pressure in particular, continues to increase throughout the global population at an increasingly fast pace. The relationship between arterial hypertension and periodontitis has been recently discussed in the context of its origins and implications. Particularly relevant is the role of the periodontal microbiome linked to persistent local and systemic inflammation, along with other risk factors and social determinants of health. The present protocol will investigate/assess the association between periodontal disease and its microbiome on the onset of hypertension, within a cohort from Mexico City. One thousand two hundred twelve participants will be studied during a 60-month period. Studies will include analysis of periodontal conditions, sampling and sequencing of the salivary and subgingival microbiome, interviews on nutritional and lifestyle habits, social determinants of health, blood pressure and anthropometric measurements. Statistical associations and several classic epidemiology and machine learning approaches will be performed to analyze the data. Implications for the generation of public policy—by early public health interventions or epidemiological surveillance approaches—and for the population empowerment—via the establishment of primary prevention recommendations, highlighting the relationship between oral and cardiovascular health—will be considered. This latter set of interventions will be supported by a carefully planned science communication and health promotion strategy. This study has been registered and approved by the Research and Ethics Committee of the School of Dentistry, Universidad Nacional Autónoma de México (CIE/0308/05/2019) and the National Institute of Genomic Medicine (CEI/2020/12). The umbrella cohort was approved by the Institutional Bioethics Committee of the National Institute of Cardiology-Ignacio Chavez (INC-ICh) under code 13-802.